Effect of a Band-Gap Gradient on the Radiative Losses in the Open-Circuit Voltage of Solar Cells - Sevan Gharabeiki; Francesco Lodola; Tilly Schaaf; Taowen Wang; Michele Melchiorre; Nathalie Valle; Jérémy Niclout; Manha Ali; Yucheng Hu; Gunnar Kusch; Rachel A. Oliver; Susanne Siebentritt (PRX Energy)
The radiative open-circuit voltage loss in a solar cell occurs because the absorptance spectrum near the band gap shows a gradual increase rather than a sharp step-function-like transition. This broadening effect has been attributed to band-gap fluctuations and/or to Urbach tails. In this work, we use modeling based on Planck’s generalized law to distinguish between these two effects. Our results demonstrate that Urbach tails have only a minimal effect on the absorptance-edge broadening and clarify that even an ideal direct semiconductor, with no band-gap fluctuations, shows broadening at the absorptance onset. Furthermore, state-of-the-art inorganic thin-film solar cells often incorporate a band-gap gradient across their thickness, which can further contribute to the absorptance broadening. Using Cu(In,Ga)Se_{2} (CIGSe) absorbers as a case study, we perform a comprehensive analysis of voltage losses through absolute photoluminescence and electroluminescence spectroscopy, combined with photospectrometry and high-spatial-resolution cathodoluminescence measurements. This study has two main purposes: (i) to present a detailed loss analysis based on Planck’s generalized law and (ii) to quantify the radiative losses arising from the band-gap gradient. We find that the loss analysis based on the combination of radiative, generation, and nonradiative losses covers the entire losses and does not leave out any other significant contribution. Samples with a graded band-gap profile show more pronounced broadening of the absorptance onset and up to 16 mV higher radiative losses compared to the samples with uniform band gap. There is also an indication that band-gap-graded samples have larger lateral band-gap inhomogeneity. Needs text.